ANALISIS RHODAMIN B PADA LIPSTIK YANG BEREDAR DI PASAR KOTA MANADO - Mamoto, Lidya Valda; Fatimawali, Fatimawali; Citraningtyas, Gayatri (PHARMACON, 2013)
Rhodamin B is a synthetic dye that banned for use in cosmetics and is certified as a hazardous material according to Minister of Health of Indonesian Republic No. 376/Menkes/Per/1990 because it cause liver damage, kidney and lymph glands damage, followed with anatomy changes such as organ enlargement. Rhodamin B dye is often used for food and beverage products. The study was conducted to identify Rhodamin B in lipstick in the market of Manado City. Samples was taken from 3 main market in Manado city, namely Karombasan market, Pasar 45 market, and Bersehati market. Samples were soaked with amonia solution, then using wool yarn to extract rhodamin B dye, followed by identification using thin layer chromatography (TLC) then detected with UV light 254 and 366 nm. Rhodamin B was evaluated using UV-Vis spectrophotometry. The result shows that 9 examined samples doesn’t contain rhodamin B Keywords : Rhodamin B, Lipstick, thin layer chromatography (TLC), UV-Vis Spectrophotometry.